2020
DOI: 10.3389/fpubh.2020.00501
|View full text |Cite
|
Sign up to set email alerts
|

Community Care in Reach: Mobilizing Harm Reduction and Addiction Treatment Services for Vulnerable Populations

Abstract: Opioid overdoses killed 47,600 people in the United States in 2017. Despite increasing availability of office-based addiction treatment programs, the prevalence of opioid overdose is historically high and disproportionately affects vulnerable populations, including people experiencing homelessness. Despite availability of effective treatment, many at greatest risk of death from overdose experience myriad barriers to care. Launched in 2018, the Community Care in Reach mobile health initiative uses a data-driven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 5 publications
(8 reference statements)
2
17
0
Order By: Relevance
“…Harm reduction specialists can potentially bridge these gaps in care and offer an accessible and patient-centered model of care delivery. Harm reduction specialists, who often have lived experience with drug use, continue to refine their expertise by working with clients in the community setting [ 29 ]. When these harm reduction specialists enter the hospital setting, they bring those skills and relationships with them.…”
Section: Discussionmentioning
confidence: 99%
“…Harm reduction specialists can potentially bridge these gaps in care and offer an accessible and patient-centered model of care delivery. Harm reduction specialists, who often have lived experience with drug use, continue to refine their expertise by working with clients in the community setting [ 29 ]. When these harm reduction specialists enter the hospital setting, they bring those skills and relationships with them.…”
Section: Discussionmentioning
confidence: 99%
“…MHUs have been used in studies to link high risk individuals to OUD, HIV, and HCV prevention and treatment services as described in Table 2, with only one focused specifically on a CJ-involved population. A demonstration study by Regis, et al provided undomiciled individuals with an elevated risk of opioid overdose the opportunity to use a MHU, placed in "hotspots" where overdoses commonly occurred, to easily access harm reduction services, addiction treatment, and other medical care (Regis et al, 2020). Another study demonstrated the role of MHUs in the distribution of naloxone, overdose education and prevention services for high-risk CJ-involved individuals, as well as linkage to general health care (Maxwell, Bigg, Stanczykiewicz, & Carlberg-Racich, 2006).…”
Section: Mobile Health Units (Mhus)mentioning
confidence: 99%
“…State agencies and harm reductionists should partner with county health departments and community-based organizations in those regions of rural Appalachia that are highly vulnerable (13) to overdose mortality and currently lack access (14) to OEND programs and other harm reduction services. Mobile harm reduction and treatment services (34,35) may be particularly effective in reaching small, at-risk communities where brick and mortar programs may not be feasible. Finally, to enhance access to harm reduction services in rural Appalachia, state o cials must reverse regulations that currently prohibit pharmacy-based naloxone distribution by mail (36).…”
Section: Willingness To Participate In An Overdose Prevention Trainingmentioning
confidence: 99%